An identity authentication scheme based on cloud computing environment. Issue 4 (February 2018) - Zhang, Manjun; Ma, Zheng; Zhang, Yan; Wang, Yongbin
Abstract In order to solve the shortcomings of traditional identity authentication technology, such as low security, low efficiency, a mobile terminal identity authentication scheme based on cloud computing environment is proposed in this paper. In addition, the two-dimensional code technology is used for identity authentication in the cloud computing environment, and the QR coding technology is also used. The dynamic authentication of the mobile terminal is realized by using the two-dimensional code as the information transmission carrier. According to the security analysis, the scheme has simple structure and no need to use the third party equipment, which has high security and adaptability. Finally, the two fusion of two-dimensional code proposed in this paper provides a new way of thinking for the identity authentication based on the cloud environment, and also promotes the development of the Internet of things.